2022
DOI: 10.1007/s40097-022-00476-3
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric nanoparticles and nanomicelles of hydroxychloroquine co-loaded with azithromycin potentiate anti-SARS-CoV-2 effect

Abstract: The outbreak of coronavirus (COVID-19) has put the world in an unprecedented scenario. To reestablish the world routine as promote the effective treatment of this disease, the world is looking for new (and old) drug that can efficiently kill the virus. In this study, we have developed two nanosystems: polymeric nanoparticles and nanomicelles-based on hydroxychloroquine and azithromycin. The nanosystem was fully characterized by AFM and DLS techniques. Also, the nanosystems were radiolabeled with 99… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…The ongoing pandemic crisis caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remains a serious global health problem, in which the absence of specific therapeutic regimens greatly contributes to the high mortality and morbidity associated with coronavirus disease 2019 (COVID-19). [26,159] Alveolar macrophages are a crucial primary line of defense against invaders, which express specific membrane receptors involved in cytokine uptake and binding of the spike protein on the coronavirus surface, thus suppressing virus infection by diverting them from target cells and blocking viral cellular entry, while mitigating the excessive inflammatory and immune responses. In a recent effort to develop a multifunctional biomimetic nanosystem against COVID-19 infection, polymeric PLGA NP cores containing 2TPE-2NDTA, an efficient photothermal agent, were wrapped with alveolar macrophage-derived membranes (Figure 17A).…”
Section: Viral Infectionsmentioning
confidence: 99%
“…The ongoing pandemic crisis caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remains a serious global health problem, in which the absence of specific therapeutic regimens greatly contributes to the high mortality and morbidity associated with coronavirus disease 2019 (COVID-19). [26,159] Alveolar macrophages are a crucial primary line of defense against invaders, which express specific membrane receptors involved in cytokine uptake and binding of the spike protein on the coronavirus surface, thus suppressing virus infection by diverting them from target cells and blocking viral cellular entry, while mitigating the excessive inflammatory and immune responses. In a recent effort to develop a multifunctional biomimetic nanosystem against COVID-19 infection, polymeric PLGA NP cores containing 2TPE-2NDTA, an efficient photothermal agent, were wrapped with alveolar macrophage-derived membranes (Figure 17A).…”
Section: Viral Infectionsmentioning
confidence: 99%
“…systems for disease treatment related to SARS-CoV-2 virus Polymeric nanoparticles are another type of carrier widely used in drug delivery systems to treat diseases related to the SARS-CoV-2 virus. These nanoparticles are composed of biocompatible and biodegradable polymers [104,105], such as poly(lactic-co-glycolic acid) (PLGA) [77], polyethylene glycol (PEG) [106], or chitosan [107]. Polymeric nanoparticles can encapsulate a wide range of drugs, including antiviral agents [104], antibodies [108], or nucleic acids [109], protecting them from degradation and improving their stability [77,106].…”
Section: Polymeric Nanoparticles In Drug Deliverymentioning
confidence: 99%
“…The radiolabelling of the NPs with a direct method can also be performed with a short incubation between SnCl 2 and the NPs, followed by the addition of 99m Tc in the solution. This method was used to radiolabel several types of NPs: octreotide NPs, cerium oxide NPs (CeO 2 -NPs), mesoporous silica NPs, poly-γ-glutamic acid NPs conjugated with folic acid, carbon-based mesoporous NPs, zirconium NPs, serum albumin nanoparticles, polymeric NPs, and dendrimer glycoconjugate [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. All the studies showed a high final LE, but the formation of radiocolloids often requires further purification of the solution.…”
Section: Radiolabelling Of Nps For Spect Imagingmentioning
confidence: 99%